Navigating Faith and Identity: The History of Catholic Community in Pugeran Parish of Yogyakarta, 1934-1968 - Gregorius Andika Ariwibowo; Hary Ganjar Budiman (Paramita: Historical Studies Journal, 2026)
Abstract: This study examines the history and evolution of the Catholic Church in Pugeran Parish, Yogyakarta, from 1934 to 1968, with particular attention to the ways in which the Church integrated Javanese cultural elements into its practices and architecture. By fostering a unique Catholic–Javanese identity, the Church became both a symbol and an agent of cultural synthesis in the region. Employing a historical methodology, this research draws on primary and secondary sources—including periodicals, commemorative books, and oral histories—to trace the development of this distinctive identity. The findings demonstrate that the Pugeran Catholic Church, established in 1934, played a key role in blending Catholicism with local Javanese culture, thus reflecting the coexistence and mutual enrichment of religious and cultural diversity. Beyond serving as a place of worship, the Church also functioned as a center for community engagement and social services, embodying an inclusive approach to both faith and culture. This integration enabled the Church to navigate significant sociopolitical changes, especially during the post-independence era, thereby establishing it as a prominent religious and community institution in Yogyakarta. Importantly, the process of inculturation was not merely a strategy for indigenizing Catholic liturgy, but also a complex negotiation of identity—between being Catholic and being Javanese—shaped by the broader dynamics of postcolonial nation-building. Abstrak: Artikel ini mengkaji sejarah dan perkembangan Gereja Katolik Paroki Pugeran, Yogyakarta, dari tahun 1934 hingga 1968, dengan perhatian khusus pada cara Gereja mengintegrasikan unsur-unsur budaya Jawa ke dalam praktik dan arsitekturnya. Dengan membangun identitas Katolik–Jawa yang khas, Gereja menjadi simbol sekaligus agen sintesis budaya di kawasan tersebut. Menggunakan metodologi sejarah, penelitian ini memanfaatkan sumber primer dan sekunder—termasuk majalah, buku peringatan, dan sejarah lisan—untuk menelusuri perkembangan identitas khas ini. Hasil penelitian menunjukkan bahwa Gereja Katolik Pugeran, yang berdiri sejak 1934, memainkan peran penting dalam memadukan Katolik dengan budaya Jawa, sehingga mencerminkan koeksistensi dan saling memperkaya antara keragaman agama dan budaya. Selain berfungsi sebagai tempat ibadah, Gereja juga menjadi pusat keterlibatan komunitas dan layanan sosial, mewujudkan pendekatan inklusif terhadap iman dan budaya. Integrasi ini memungkinkan Gereja menghadapi perubahan sosial-politik yang signifikan, khususnya pada era pascakemerdekaan, sehingga menempatkannya sebagai institusi religius dan komunitas yang menonjol di Yogyakarta. Penting untuk dicatat, proses inkulturasi ini bukan sekadar strategi mengindonesiakan liturgi Katolik, melainkan negosiasi kompleks identitas—antara menjadi Katolik dan menjadi Jawa—yang dibentuk oleh dinamika lebih luas pembangunan bangsa pascakolonial.